Antibacterial activity of methanolic crude extracts from selected plant against Bacillus cereus - Mustafa, Muskhazli; Mokhtar, Dirnahayu; Abd Aziz, Nor Azwady; Y., Nurhafiza; E., Nor Dalilah; Che Ku Nordin, Che Ku Nurshaira (Universiti Putra Malaysia, 2009)
Bacillus cereus is a well-known food-poisoning bacterium. In this study, six methanolic crude extracts, from Azadirachta indica, Choromolaena odorata, Justicia gendarussa, Mangifera odorata, Strobilanthes crispus and Tinospora crispa, were investigated for their antibacterial activities against B. cereus. For this purpose, different concentrations of the methanol solvent crude extract from selected plants were used (1, 2, 4, 6, 8, 10, 15, and 20 mg/ml) and the diameter of B. cereus growth inhibition zone was measured at every 24 hours for 5 days. The antibacterial assay for all the crude extracts showed the inhibition of B. cereus growth by concentrations ranging from 2 mg/ml to 20 mg/ml, with a significant correlation between the extract concentrations and degrees of antibacterial activity. Rapid formation of inhibition zones within 24 hours of incubation was obtained, before a slight reduction in the inhibition of the diameter of zone was observed after 120 hours of incubation. The Minimal Inhibition Concentration (MIC) value for J. gendarussa, M. odorata and S. crispus crude extracts were at 2 mg/ml, while A. indica, C. odorata and T. crispa were at 6 mg/ml, 8mg/ml and 10 mg/ml, respectively. However, the Minimal Bactericidal Concentration (MBC) for all the crude extracts were at much higher concentration with the crude extract of J. gendarussa, M. odorata and S. crispus obtained the MBC values at 6mg/ml, whereas A. indica, C. odorata and T. crispa were at 10 mg/ml.